EFFECTIVENESS OF LASER VISION CORRECTION FOR MYOPIA AND ITS PREDICTORS - Aliyeva, S.Sh. (World of Medicine and Biology, 2025)
The purpose of the study was to evaluate the effectiveness of laser vision correction for myopia depending on the demographic and clinical profile of patients in order to identify predictors of surgical outcomes. A total of 54 patients with myopia were observed, with an average age of 29.6±0.5 years. Vision correction was performed on 108 eyes using an excimer laser. All patients underwent topographic examination before the surgery and again three months postoperatively. The assessment of safety, predictability, and effectiveness of laser vision correction for myopia based on various criteria leads to consistent conclusions. Three months after laser vision correction, stable treatment outcomes were established: safety – 92.6±2.5 %, predictability – 88.0±0.1 %, effectiveness – 92.6±2.5 %, and stability – 92.6±2.5 %. The results of laser vision correction for myopia depend on the severity of myopia, the patient’s age, preoperative visual acuity, and keratotopographic parameters (ISV, IVA, df, db, RPI, ART, RMS).